Natural antitumor resistance of the organism condition of patients with uveal melanoma of small sizes - Polyakova, S.I.; Velichko, L.N.; Bogdanova, A.V.; Tsukanova, I.V. (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The role of immune mechanisms in the tumor process development and progression is currently beyond any doubt. In this regard, the study of the immune system of patients with choroidal melanoma (CM) is very important at the initial stage of the disease specifically, i. e. CM of small sizes (protruding up to 3 mm), that in general can have a positive effect in the implementation of therapeutic pathomorphism in applying various treatment methods. Purpose. To examine the immune system condition in patients with CM of small sizes in comparison with healthy individuals control group. Materials and Methods. An immunological research was implemented in 35 patients with UM of small sizes before the treatment. These were the patients of SI "The Filatov Institute of Eye Diseases and Tissue Therapy of NAMS of Ukraine" (treatment group) and 44 healthy people (control group). The average age of the patients in the treatment group and the control group was (53.9 ± 12.1) and (55.4 ± 11.5) respectively. In the treatment group, there were 26 women (74.3%) and 9 (25.7 %) men. In the control group, there were 26 (59.1%) women and 18 (40.9%) men. In both groups, cellular and humoral immunity components were studied in accordance with generally accepted methods. Results. Most indicators of both cellular and humoral immunity in patients with CM of small sizes were higher than in healthy individuals. So CM-patients at the initial stage of the disease in comparison with healthy people had a statistically significant increase of such indicators, as the absolute cells count (by 17.5%, p = 0.005), T-lymphocytes CD3+ absolute count (18.6%, p = 0.04), cytotoxic cells CD8+ absolute count (57.9%, p = 0.002), immunoregulatory index ratio CD4+/CD8+ (82.9%, p = 0.00002), immunoglobulin A (30.2%, p = 0.003) and M (21.4% p = 0.0007). At the same time, there was a statistically significant minor (2.8%, p = 0.04) decrease of the relative count of T-lymphocytes CD3+. This indicates that at the initial stage of UM progression, patient’s immune system is active. An increase of absolute (46.3%, p = 0.0004) and relative (by 21.5%, p = 0.007) phagocytic neutrophils activity also indicates the natural resistance of UM-patients at an early stage of the disease. Conclusions. Uveal melanoma initial stage is accompanied with cellular and humoral specific immunity activation and enhanced antitumor resistance of the organism.